The neonatal levels of TSB, NSE and CK-BB in autism spectrum disorder from Southern China - Lv Meng-na (De Gruyter, 2016)
Background" Autism spectrum disorder (ASD) is a serious neurodevelopmental disorder that impairs a child’s ability to communicate with others. It also includes restricted repetitive behaviors, interests and activities. Symptoms manifest before the age of 3. In the previous studies, we found structural abnormalities of the temporal lobe cortex. High spine densities were most commonly found in ASD subjects with lower levels of cognitive functioning. In the present study, we retrospectively analyzed medical records in relation to the neonatal levels of total serum bilirubin (TSB), neuron-specific enolase (NSE), creatine kinase brain band isoenzyme (CK-BB), and neonatal behavior in ASD patients from Southern China. Methods: A total of 80 patients with ASD (ASD group) were screened for this retrospective study. Among them, 34 were low-functioning ASD (L-ASD group) and 46 were high-functioning ASD (H-ASD group). Identification of the ASD cases was confirmed with a Revised Autism Diagnostic Inventory. For comparison with ASD cases, 80 normal neonates (control group) were selected from the same period. Biochemical parameters, including TSB, NSE and CK-BB in the neonatal period and medical records on neonatal behavior were collected. Results: The levels of serum TSB, NSE and CK-BB in the ASD group were significantly higher when compared with those from the control group (P < 0.01, or P < 0.05). The amounts of serum TSB, NSE and CK-BB in the L-ASD group were significantly higher when compared with those in the H-ASD group (P < 0.01, or P < 0.05). The Neonatal Behavioral Assessment Scale (NBAS) scores in the ASD group were significantly lower than that in the control group (P < 0.05). Likewise, the NBAS scores in the L-ASD group were significantly lower than that in the H-ASD group (P < 0.05). There was no association between serum TSB, NSE, CK-BB and NBAS scores (P > 0.05) in the ASD group. Conclusions: The neonatal levels of TSB, NSE and CK-BB in ASD from Southern China were significantly higher than those of healthy controls. These findings need to be investigated thoroughly by future studies with large sample.